Simulation of dynamic absorbed energy analysis of multi-cell aluminum 6061-t6 alloy extrusion / Akbar Othman and Mohd Fahrul Hasan - Othman, Akbar; Hasan, Mohd Fahrul (2012)
The crushing simulation is presented in this paper to determine the dynamic absorbed energy of multi-cell aluminum 6061-T6 alloy extrusion tubes under axial loading. Thin-walled extruded aluminum 6061-T6 alloy tubes were widely used as energy absorbers for decades since they have an advantage in terms of strength to weight ratio efficiency. The presented paper deals with identifying the influence of the variety of cell on thinwalled tubing as well as variables wall-thickness and velocity impact when subjected to dynamic axial loading. The main focus was on improvement of crush energy absorption of structures in frontal crush impact cars. The numerical simulations of thin-walled tubes were modeled and analyzed using LS-DY@A commercial finite element software. The validation was carried out based on numerical studies from reference literature to ensure that the predictions of modeling analysis were accepted. Results indicated that the thin-walled tube’s energy absorption capability was affected significantly by variations in multiple cell, velocity-impact and wall thickness.